2020
DOI: 10.1111/jnu.12551
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review: Moral Injury in Nurses in the Aftermath of a Patient Safety Incident

Abstract: Background To date, there has been no published work towards understanding or classifying patient safety incidents (PSIs) or their aftermath as potential morally injurious experiences (pMIEs). A morally injurious experience is one that violates deeply held moral values and beliefs, and can put an individual at risk for burnout, post‐traumatic stress disorder, and other trauma‐related problems. This can also set the stage for moral injury, which can occur when there has been a betrayal of what is right by someo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 47 publications
2
48
0
1
Order By: Relevance
“…10,20,23,57 Ethically, nurses may experience compassion fatigue or moral injury, as they must balance their perceived responsibility to safeguard patient welfare with the fear and anxiety of getting infected and amplifying the spread of the infection. 25,57 These results are consistent with qualitative and empirical research that found many nurses feel they are being pushed beyond their limits. 12,19,21,40 Frontline nurses during this time have limited team support due to the number of professionals allowed in the room with the patient, as well as time constraints related to the suggested time nurses can be in the rooms with patients.…”
Section: Stress and Anxiety Related To Job Demand Factorssupporting
confidence: 84%
See 3 more Smart Citations
“…10,20,23,57 Ethically, nurses may experience compassion fatigue or moral injury, as they must balance their perceived responsibility to safeguard patient welfare with the fear and anxiety of getting infected and amplifying the spread of the infection. 25,57 These results are consistent with qualitative and empirical research that found many nurses feel they are being pushed beyond their limits. 12,19,21,40 Frontline nurses during this time have limited team support due to the number of professionals allowed in the room with the patient, as well as time constraints related to the suggested time nurses can be in the rooms with patients.…”
Section: Stress and Anxiety Related To Job Demand Factorssupporting
confidence: 84%
“…4,5,8,[12][13][14]24 Due to their professional obligations to provide patients with the best treatment possible, many nurses may feel the emotional and mental stress of watching their patient's health quickly deteriorate due to worsening symptoms. 9,14,25 As one nurse from the initial design phase stated:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, MI has been associated with increased medical errors among HCPs during the COVID-19 pandemic (Mantri et al, 2021a;Wang et al, 2021). It may be difficult, however, to determine whether such medical errors are the result of MI or its cause (Curlin 2005;Stovall et al, 2020).…”
Section: Healthcare Professionalsmentioning
confidence: 99%